Effect of information systems and facilities on Siskeudes benefits through user satisfaction - Hasyim, Wahid; Nugroho, Mulyanto; Hwihanus, Hwihanus (Edelweiss Applied Science and Technology, 2024)
This study evaluated the combined application of the DeLone and McLean Information Systems Success Model and the Unified Theory of Acceptance and Use of Technology (UTAUT) in the context of the Village Financial System (SISKEUDes) in Berau Regency. The research found that information system quality significantly influenced user satisfaction and intentions to use the system but did not significantly impact net benefit. Facilitating conditions positively affected user satisfaction but did not significantly influence intentions to use or net benefit. Habit was found to significantly impact net benefit, though it did not affect user satisfaction or intentions to use. Furthermore, user intentions were identified as a significant mediator in the relationship between system quality, facilitating conditions, habit, and net benefit. These findings highlight the crucial role of user intentions in determining the net benefits of SISKEUDes and suggest areas for improvement in system management and implementation.